PENGUJIAN NUTRIEN ANORGANIK UNTUK BIOREMEDIASI TUMPAHAN MINYAK MENTAH DENGAN METODE BIOSTIMULASI DI LINGKUNGAN PANTAI SURABAYA TIMUR - Munawar Munawar (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
Bioremediation is an application of biological processes to treat ground water, soil, and mud contaminated with hazardous chemical. In this study, inorganic nutrient of commercial NPK fertilizer was applied. Crude oil was from Pertamina oil source of Cepu, Center Java. Crude oil was applied based on a consideration that many oil spill accidents spilled crude oil. The site was coastal area in Keputih, Sukolilo, Eastern Surabaya. In the study, experimental squares of 0,5 m x 0,5 m was made, each square had 0,25 m space. There were 18 experimental squares and one control square. Variables consist of nutrient level (0,2; 0,3; and 0,4 kg/square) and soil treatment (tilled and not). It was observed from study that inorganic nutrient significantly affected the decrease of crude oil concentration. It was also observed that tilled soil resulted in better effect and could decrease oil concentration until 36,61%. Otherwise, untilled soil decreased only 32,33%.